Lessons Learned on the Application of Vibration Absorbers for Enhanced Cannon Stabilization - Eric Kathe (Shock and Vibration)
This paper will summarize the successful application of muzzle-end vibration absorbers to reduce cannon vibration. This technology constitutes a weapons stabilization approach that focuses on passive mechanical structural modification of the cannon, rather than relying upon an external control law to actively cancel vibrations. Challenges encountered during field testing, non-ideal behavior, and performance evaluation using digital signal processing will be highlighted.